ANALISIS PERKEMBANGAN PESERTA DIDIK MENURUT TEORI JEAN PIAGET DAN PENGIMPLEMENTASIANYA PADA PEMBELAJARAN IPA SMP - Anggraeni, Nur Diyati; Kumala Dwi Alviana, Waviq; Fitriya Wahyuni, Desy; Kusuma Ainurrosyidah, Linda Dwi; Mahardika, I ketut; Sutarto, Sutarto; Wicaksono, Iwan (STKIP PGRI Situbondo, 2024)
Cognitive development starts from concrete thinking processes to higher levels, namely abstract and logical concepts. According to Piaget, children are naturally interested in the world and actively seek information that can help them understand that world. This research aims to describe students' cognitive development based on Jean Piaget's theory of development and how it is implemented in science learning at junior high school level. This research uses qualitative research methods with a descriptive analysis approach. This means that in this research the researcher chose to use primary and secondary sources (books, journals, websites, etc.) regarding developmental theory according to Jean Piaget as a source of research data. This research focuses on the implications or involvement of students' cognitive development in science learning based on Jean Piaget's theory. The research results show that implementing Piaget's theory can help educators understand the stages and characteristics of students' cognitive development so they can determine cognitive levels and choose learning strategies that are appropriate to students' stages of development.